TRANSFORMASI SISTEM PELAYANAN BEBAS PUSTAKA DI UPT PERPUSTAKAAN UNIVERSITAS NEGERI BENGKULU - Nadia, Riska (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2024)
Free library service is a service in the library, this service can help students to inform that students are free from borrowing collection materials in the library or explain that students are not subject to fines in the library which are explained in the form of a letter. System transformation in services is a change in procedures or requirements in the service. In this case, the transformation of the free library service system really helps students in carrying out the free library process where they can register for free libraries online which can be accessed by students wherever and whenever they are and is also useful for librarians to improve their performance and their rest time is not disturbed. The purpose of this research itself is to see what kind of procedures have undergone these changes, especially the free library service procedures. The method used in this research is the Qualitative Description Method by conducting direct interviews with a librarian named Mrs. Lili Haryanti, S.I.Pust. This research was conducted at the Bengkulu State University Library UPT.